Tanggung Jawab Pribadi dalam Kasus Pungutan Liar yang Dilakukan oleh Pegawai Negeri Sipil - Nurmalita Ayuningtyas Harahap (Undang: Jurnal Hukum, 2019)
This study analyzes about the responsibilities of civil servants (PNS) who does cases of illegal levies. The problem formulation is why do PNS who does illegal levies will be subject to personal responsibility not job responsibilities. This article concludes that violations of norms committed by PNS will incur legal consequences in the form of responsibility to the injured party. The norms that must be obeyed by civil servants in carrying out their duties are the norms of government (bestuursnorm) and norms of behavior (gedrasnorm). Accountability for violations of government norms will later be directed to government positions, with compensation imposed on agencies, with a touchstone using the principles of legality, principles of specialty, and general principles of good governance. While accountability for violations of the norms of behavior will be addressed to the relevant office holders or civil servants, with a touchstone using maladministration. Illegal levies are included in the category of maladministration, therefore in conducting maladministration which is a violation of the norms of behavior will cause legal consequences in the form of personal responsibility. Abstrak Artikel ini membahas tentang tanggung jawab pegawai negeri sipil (PNS) yang melakukan kasus pungutan liar. Permasalahan yang dibahas adalah mengapa PNS yang melakukan pungutan liar dikenakan tanggung jawab pribadi dan bukan tanggung jawab jabatan. Artikel ini menyimpulkan bahwa pelanggaran norma yang dilakukan oleh PNS akan menimbulkan konskuensi hukum berupa tanggung jawab kepada pihak yang dirugikan. Adapun norma yang yang harus dipatuhi pegawai negeri sipil dalam melaksanakan tugasnya adalah norma pemerintahan (bestuursnorm) dan norma perilaku (gedrasnorm). Pertanggungjawaban terhadap pelanggaran norma pemerintahan tersebut nantinya akan ditujukan kepada jabatan pemerintahan, dengan ganti rugi dibebankan kepada instansi, dengan batu uji menggunakan asas legalitas, asas spesialitas, dan asas-asas umum pemerintahan yang baik. Sedangkan pertanggungjawaban terhadap pelanggaran norma perilaku akan ditujukan kepada pemangku jabatan atau PNS yang bersangkutan, dengan batu uji menggunakan maladministrasi. Pungutan liar termasuk dalam kategori perbuatan maladministrasi, oleh karena itu dalam melakukan maladministrasi yang merupakan pelanggaran terhadap norma perilaku akan menimbulkan konsekuensi hukum berupa tanggung jawab pribadi.